Characterization, stability and rheology of highly concentrated monodisperse emulsions containing lutein. (July 2015) - Matos, M.; Gutiérrez, G.; Iglesias, O.; Coca, J.; Pazos, C.
Abstract: Highly concentrated oil-in-water (O/W) emulsions, also called high internal (or dispersed) phase emulsions (HIPEs), containing lutein, were prepared using a two-stage process: membrane emulsification (ME) and further vacuum evaporation. Monodisperse HIPEs with controlled droplet size, a water volume fraction (fw ) of 0.25, and encapsulation efficiency (EE) up to 97% were obtained. Membranes such as Shirasu porous glass (SPG), ceramic, and metallic were used in the first stage, yielding emulsions with fw of 0.84 and controlled droplet size. Final concentrated emulsions (fw  = 0.25) were obtained by vacuum evaporation. Emulsions were formulated with two different food-grade oils (soybean oil and miglyol) and a non-ionic surfactant Tween 20, 2% (w/w). Sodium carboximethylcellulose (CMCNa) in the range of 0.1–0.5 % (w/w) was used as hydrocolloid stabilizer. Emulsions were characterized in terms of rheology, stability, droplet mean diameter, and efficiency of lutein encapsulation. Rheological properties of HIPEs and dilute emulsions resulting from ME stage were also compared. Results showed that emulsion viscosity, as well as their rheological properties, depended greatly on oil droplet diameter and dispersed phase concentration. However, the effect of oil droplet diameter on viscoelastic behavior was considerably larger for HIPEs than for dilute emulsions. CMCNa increased emulsion viscosity and also improved stability of oil droplets. The highest viscosity value and dynamic viscoelastic functions were obtained for HIPEs with the smallest droplet mean diameter. HIPEs exhibited high stability and large creaming resistance making them suitable for their use in functional foods or cosmetic products. Graphical abstract: Highlights: HIPEs with controlled droplet size were prepared by ME and further vacuum evaporation. Lutein-containing HIPEs exhibited high encapsulation efficiencies (97%). HIPEs showed good stability, creaming resistance and rheological properties. These characteristics make HIPEs suitable as lutein delivery systems.